Analysis of Marketing Stimuli Factors in Purchasing Decisions for Fast Fashion Items Among Generation Z in Batam - Puspitasari, Ayu; Dwinurcandra, Winda Kawa; Efionita, Yolanda (Journal of Applied Business Administration, 2025)
This study aims to analyze the marketing stimuli factors that influence the purchasing decisions of Generation Z in Batam City regarding fast fashion items. The research adopts a quantitative approach, utilizing factor analysis as the primary analytical method. Within the study, 19 variables were initially examined and subsequently reduced to several factors. The analysis revealed four key factors that drive purchasing decisions for fast fashion items among Generation Z in Batam City: Attractive Service, Marketing Excellence and Competitive Design, Value for Money, and Shopping Experience. The Attractive Service factor emerged as the most dominant, accounting for 24.192% of the variance in this study. This finding underscores the critical role of service quality in influencing consumer decisions in the competitive fast fashion industry. Brands should strengthen their digital presence through engaging social media content, and ensure up-to-date product designs to align with Generation Z’s preferences for developing competitive strategies. Additionally, improving the shopping experience through accessible store locations, strengthening brand reputation, and creating an inviting store atmosphere, can further attract and retain Generation Z consumers in Batam’s competitive market.